The Monte Carlo method of random simulation samples - Gaytán Cortés, Juan (Mercados y Negocios, 2023)
The Monte Carlo method is one of the most powerful mathematical techniques that, through calculation, analyzes risk and allows solving physical and mathematical problems through computer programs. Using historical data creates and predicts models of possible future results by substituting a range of values, calculating results repeatedly, and using a different group of random values of the probability functions to predict the potential effects of some uncertain event related to problems of all kinds.